HUBUNGAN KELINCAHAN TERHADAP KEMAMPUAN DRIBBLE BOLA BASKET PADA TIM PUTRI SMAN 3 MANDAU - Sri Wulan Fajrianti; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this research is that the ball is always outoff control of the possession, too difficult to break through the opponent's defense, the lack of ability to outwit the opponent with a certain motion attraction such as crossover, spin dribble without losing the balance of the body while breaking through to score. The purpose of this research is to determine whether there is a relationship of agility to the ability of dribble on the girl's basketball team SMAN 3 Mandau. The population in this study are all basketball players SMAN 3 Mandau totaling 12 people. Instruments in this research is dooging run test and dribbling test. Data obtained in analysis by using a technique of correlation product moment. Based on the results of research and processing data by using research statistics procedure, so it is can conclude that to the correlation between X variable with Y variable obtained score r = 0,714 so rxy > rtabel that is ( 0,714 > 0,602 ), so Ha be accepted, in the other words there is has correlation that significant between agility of dribbling on the girl's basketball team SMAN 3 MandauKeywords: Agility, Dribbling ability.